Land, labour & rights : 10 Daniel Thorner memorial lectures - Thorner, Alice, 1917- (New Delhi : Tulika, 2001)
Contributed articles with special reference to India.
"Daniel Thorner memorial lecture."
Includes bibliographical references and index.
Keywords: Land tenure -- India; Land reform -- India; Agricultural laborers -- India